1993
DOI: 10.4049/jimmunol.150.2.644
|View full text |Cite
|
Sign up to set email alerts
|

Soluble E-selectin is found in supernatants of activated endothelial cells and is elevated in the serum of patients with septic shock.

Abstract: A quantitative sandwich ELISA for E-selectin in the fluid phase (soluble E-selectin, sEs) has been developed that is sensitive to 100 pg/ml. The assay shows no reactivity with either L- or P-selectins. We have used this to determine the fate of E-selectin after cell-surface expression and to test whether levels measured in vivo may represent the state of endothelial activation. E-selectin was first detectable in supernatants of IL-1-stimulated endothelial cells at 24 h, and increased slowly up until 72 h. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…The correlations between sE-cadherin and ESR and IL-6 suggest a potential relationship between sE-cadherin release and systemic inflammation in SLE. In accordance with these results, it has been shown that IL-1 causes shedding of E-cadherin from the cell surface of cultured human endothelial cells 32 . In a mouse model, intratracheal antigen or lipopolysaccharide challenge induced focal sE-cadherin release that was correlated with infiltrated neutrophil numbers 33 .…”
Section: Discussionsupporting
confidence: 78%
“…The correlations between sE-cadherin and ESR and IL-6 suggest a potential relationship between sE-cadherin release and systemic inflammation in SLE. In accordance with these results, it has been shown that IL-1 causes shedding of E-cadherin from the cell surface of cultured human endothelial cells 32 . In a mouse model, intratracheal antigen or lipopolysaccharide challenge induced focal sE-cadherin release that was correlated with infiltrated neutrophil numbers 33 .…”
Section: Discussionsupporting
confidence: 78%
“…Soluble forms of E-selectin have been found in supernatants of cytokine-stimulated endothelial cells in culture [88,89]. Low serum levels are present in healthy subjects, and elevated levels were detected in patients with septic shock [89].…”
Section: Soluble Adhesion Moleculesmentioning
confidence: 99%
“…Soluble E-selectin (sE) is present in the supernatants of cultured endothelial cells activated by interleukin-1␤, and the serum level of sE is elevated in patients with septic shock [8]. Thus, it is possible that serum levels of sE may reflect cytokine-induced endothelial cell activa-tion, which leads to disseminated intravascular coagulation (DIC) in the presence of sepsis.…”
Section: Introductionmentioning
confidence: 99%